Stone cold - Box, C. J. (Box, C. J. Joe Pickett novel, 2015)
"The electrifying new Joe Pickett novel from the New York Times-bestselling author. Everything about the man is a mystery: the massive ranch in the remote Black Hills of Wyoming that nobody ever visits, the women who live with him, the secret philanthropies, the private airstrip, the sudden disappearances. And especially the persistent rumors that the man's wealth comes from killing people. Joe Pickett, still officially a game warden but now mostly a troubleshooter for the governor, is assigned to find out what the truth is, but he discovers a lot more than he'd bargained for. There are two other men living up at that ranch. One is a stone-cold killer who takes an instant dislike to Joe. The other is new-but Joe knows him all too well. The first man doesn't frighten Joe. The second is another story entirely"--Provided by publisher of hardcover edition.